Extraction of natural dye from butterfly pea flower to develop dye-sensitized solar cell to doped on magnesium oxide / Muhammad Shazwan Ruslee - Ruslee, Muhammad Shazwan (2023)
The combination of post covid recovery, depleted fossil fuel reverse and extreme weather condition led to surge in demand for energy. Solar energy is a sustainable industry that capture interest energy industry in the world. The material that most commonly used nowadays is from synthetic dye. Therefore, natural dye from plan is proposed. This is because the natural dye never pollute like synthetic dye as they are obtained. The objective of this study is to find out the best extraction time of natural dye in metal oxide, to study the presence of functional group in natural day and to study the potential of natural dye to use as solar film material. The natural dye was extracted from Butterfly Pea or the scientific name is Clitoria Ternatea (flower) using convectional extraction method and doped into metal oxide which is Magnesium Oxide (MgO) for 1 - 5 days. The result obtained had showed the concentration of dye decreasing as the time dope is increase. The natural dye is also tested with conductivity and the result showed a decreasing trend. Also, by FTIR, the longer the magnesium oxide is doped into the sample, the higher the transmittance showing the presence of O-H bonding determine the ability for the adsorption of solar energy. To conclude, natural dye from butterfly pea flower has the potential to be used for the Dye-Synthesized Solar Cells (DSSC).